In vitro evaluation of three gutta-percha solvents - Pineda Mejía, Martha Elena (2011)
The purpose of this study was to evaluate the solubility of gutta-percha in three solvents used in endodontics: xylol of traditional use, and the essential oils: eucalyptol and orange oil, of recent use, given the frequent need to remove the obturation material in radicular retreatment procedures. One hundred twenty samples of gutta-percha were prepared in a standardized way in small cylinders, being divided equally into four groups for immersion in three experimental solvents and distilled water (control group) during 2.5 and 10 minutes at room temperature. The solvent effect was recorded in grams of weight loss, calculating the difference between pre and post-immersion samples weight for each experimental time. The results were analyzed and compared by Tukey test (p <0.05). Under the conditions of this study it is concluded that, all experimental solvents were effective to dissolve gutta-percha. Xylol showed superior solvent effects in all experimental times. Orange oil and eucalyptol presented similar solvent effects.